Isolated congenital microgastria - Sarah Magdy Abdelmohsen; Tarek Abdelazeem Sabra (Elsevier, 2022)
Background: Infants with recurrent vomiting and respiratory tract infection since birth constitute a challenging diagnosis for pediatric surgeons. The surgeon must put in mind a congenital microgastria (CM) as a differential diagnosis. Case reports: A five-month-old male infant complained of non-bilious vomiting since birth. A gastrografin swallow had referred to the dilated esophagus, small capacity stomach, and the contrast flows easily distally to the duodenum. A gastric augmentation was created through a Hunt-Lawrence (HL) pouch with a good outcome. Discussion: Diagnosis of CM can be discovered during the intrauterine life through the absence of visualization of the gastric gas. CM may be associated with other anomalies or may be isolated. The isolated anomaly should operate early, as soon as possible because the stomach will not spontaneously enlarge with the conservative management. Conclusions: HL pouch is a suitable gastric augmentation for the infant with isolated CM. The dilated esophagus returns to its normal size after increasing the stomach reservoir.